PENGARUH BELANJA DAERAH TERHADAP PERTUMBUHAN EKONOMI DAERAH KABUPATEN SUMBAWA BARAT - Mutiatul Jannah; K Kurniawansyah; I Ismawati (Pusat Riset dan Publikasi, 2022)
This study aims to determine the effect of regional spending on economic growth in West Sumbawa Regency. This type of research is explanatory research conducted to examine the relationship or influence of the variables studied, namely regional spending on regional economic growth in West Sumbawa Regency. The type of data used is quantitative data in the form of capital expenditure data and economic growth for West Sumbawa Regency for 2012-2021 obtained from documents and archives that have been published by the West Sumbawa Regency Central Bureau of Statistics (BPS). All data that has been collected was processed using the SPSS application to be analyzed using simple linear regression analysis techniques, partial hypothesis testing (t test), and determination coefficient test (R2). The conclusion drawn from this study is that regional spending has a positive and significant effect on regional economic growth in West Sumbawa Regency. the ability of regional expenditure variables to influence variations in changes in regional economic growth variables in West Sumbawa Regency is 25.9%, while the remaining 74.1% is influenced by other variables beyond the scope of this study.